Wireless and Cellular Telecommunications - C.Y.LEE William (McGraw -Hill, 2005)
The wireless pioneer William C.Y. Lee, technology leader and author of the #1 book on wireless communications, has now completely updated his classic. This all-new, in-depth engineering guide for both voice and data services, Wi-Fi, 3G, WiMAX, and more, is essential reading for anyone working in this dynamic field.